PELAKSANAAN PROSEDUR PEMUNGUTAN PAJAK REKLAME OLEH DINAS PENDAPATAN PENGELOLAAN KEUANGAN DAN ASET DAERAH (DPPKAD) KABUPATEN SIAK - Ahmad Safi'i; Ernawati " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This study will see how to Implementation Procedures Advertisement Taxation by the Departement of Finance and Asset Management Income Districts Siak. Acquisition revenue (PAD) from advertisement tax in Siak sector is potentially quite high, because there is little individual or business entity that uses advertising as a tool to promote their business. But achieving the target is still low, not as expected. Whereas in the advertisement taxation should not be difficult, sience the object and the number of its points are clear.Theory concepts used in this study was according to management theory George R Terry opinion in manullang that management can be measured by the following indicators : planning, organizing, actuating, controlling, including factors that humper the implementation of advertisement. As well as the research method used is descriptive qualitative, The next in the determination informen using technique purposive sampling.Implementation Procedures Advertisement Taxation by the Departement of Finance and Asset Management Income Districts Siak not going well in perform its function as an agency and income tex levies. Thereby affecting there reception revenue (PAD) from advertisement tax sector in regency Siak not optimal. Whereas the factors that hinder the implementation of advertisement taxation by the department of finance and asset management income areas in the are siak is the limited number of employees and also the lack of operational infrastructure as well as inadequate equipment owned by the department of finance management income asset fun districts siak. The role of the taxpayer/business advertisement tax that has not been obedient also became one of the problems that hamper implementation advertisement taxation in the district siak.Keyword : Implementation for collection, advertisement tax